2011
DOI: 10.4103/0973-1296.80671
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects on myelosuppression mice treated by three different classic chinese medicine formulae

Abstract: Background:In order to observe the protective therapeutic action and mechanism of Liuwei Dihuang Decoction, Buzhong Yiqi Decoction, and Compound Danshen Decoction on Myelosuppression induced by cyclophosphamide.Materials and Methods:The mice model was established by intraperitoneal injected with 100 mg/kg cyclophosphamide by human and mice dose conversion on the 9th, 11th, 13th days during the experiment. Flow cytometry (FCM) was used for detecting the number of cells and investigating bone marrow cell cycles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In the present study, the effects of BZ on weightlessness-induced muscle atrophy and its mechanisms were investigated. BZ is additionally commonly used in clinical practice for chronic fatigue and chronic atrophic gastritis, and is widely produced ( 12 ). Large scale epidemiological studies in clinical trials have been conducted, suggesting that BZ has a clear effect on improving muscle function ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the effects of BZ on weightlessness-induced muscle atrophy and its mechanisms were investigated. BZ is additionally commonly used in clinical practice for chronic fatigue and chronic atrophic gastritis, and is widely produced ( 12 ). Large scale epidemiological studies in clinical trials have been conducted, suggesting that BZ has a clear effect on improving muscle function ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few developing HSCs could be observed, most of which exhibited pyknotic nuclei. Similarly, other researchers reported that CY injection caused significant decrease in bone marrow cell counts ( 15 ).…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, the lowest % of CD34 +ve cells was detected in gIIa (CY only). Previous investigations revealed that AM accelerated bone marrow haemopoietic stem progenitor cells in marrow-suppressed mice and enhanced cell proliferation by promoting cell cycles from G0/G1 phase to access into S, G2 phases ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Myelosuppression is a significant side effect of most chemotherapeutic and radiotherapeutic agents [1], leading to decreased red and white blood cell populations [2] and potential immunosuppression [3]. Fatal infections may occur in severe cases [4]. Thus, myelosuppression significantly affects patient outcomes.…”
Section: Introductionmentioning
confidence: 99%